The Role of Fecal M2-Pyruvate Kinase (M2-PK) in Colorectal Cancer Screening - Nur Chandra Bunawan; Marcellus Simadibrata (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2017)
Colorectal cancer is a malignancy with high incidence and mortality rate. The long carsinogenesis sequence from adenoma unto carsinoma enable early detection and screening as part of the management but until recently the commercialy available test has low sensitivity and specificity. M2-pyruvate kinase (M2-PK), an isomer of glycolisis enzyme involved in aerobic metabolism, is found in high amount in cancerous cell and is shed unto luminal mucosa in colorectal cancer. Quantification of this protein in feces is a promising method to detect malignant lesion of colon. Several studies until recently demonstrate moderate sensitivity and specificity but clearly with better performance than commonly-used gFOBT.